THE APPLICATION OF THE SPECULAR REFLECTION OF NEUTRONS TO THE STUDY OF SURFACES AND INTERFACES - Penfold, J; Thomas, R (1990)
The application of the specular reflection of neutrons to the study of surface and interfaces is described. The theoretical and experimental background to the technique is presented. A range of recent experimental results in surface chemistry, solid films and surface magnetism is discussed. In surface chemistry the results include adsorption of surfactants at the air-solution interface, insoluble monolayers and polymers at the air-liquid interface, soap films and adsorption at the liquid-solid and liquid-liquid interfaces. In solid films results on Langmuir-Blodgett films, hard carbon films, polymer films and some semiconductor layers are discussed. In surface magnetism experimental data which illustrate the nature of magnetism in magnetic multilayers and ferromagnetic films, and which describe flux penetration in superconductors, are presented.